Ethnopedagogy E-Module Development to Accommodate the Diversity of PGMI Students' Learning Styles - Hanifah, Desty Putri (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
This study aims to develop ethno pedagogy e-modules that can accommodate the diversity of PGMI students' learning styles. The development uses the Research and Development (RD) method with the ADDIE model, involving 40 PGMI students in the 5th semester consisting of 10 students for limited trials and 30 for field trials. Learning style analysis shows a distribution of 45% visual, 30% auditory, and 25% kinesthetic. The validation results from material, media, and ethno-pedagogy experts show an excellent feasibility level, with an average score after revision reaching 3.80 (95%). The implementation of e-modules resulted in increased learning outcomes that varied based on learning styles: visual (32.5%), auditory (28.7%), and kinesthetic (27.6%), with an average total increase of 29.6%. Students' responses to the implementation of e-modules were very positive, with an average of 92.4%, covering aspects of content interest, understanding of the material, suitability of learning styles, relevance of cultural values, and learning motivation. The paired t-test showed a significant difference between the pre-test and post-test (t-count = 8.45 t-table = 2.03) at a significance level of 5%. The results of the study prove that e-module Ethno pedagogy effectively accommodates the diversity of learning styles, improves the learning outcomes of PGMI students, and successfully integrates local wisdom values in digital learning.